Reduced vascular endothelial growth factor levels in the cerebrospinal fluid in patients with treatment resistant major depression and the effects of electroconvulsive therapy: a pilot study - Kranaster, Laura; Blennow, Kaj; Zetterberg, Henrik; Sartorius, Alexander (Journal of affective disorders, 2019)
Background - Several lines of evidence are pointing towards an involvement of the vascular endothelial growth factor (VEGF) in the pathophysiology of depression. There are studies analyzing blood levels of VEGF in patients with depression compared to controls, but a data on cerebrospinal fluid (CSF) levels of VEGF in patients with depression are lacking. - Method - CSF VEGF levels were measured in patients (n=12) with a severe, treatment-resistant depressive episode before and after the antidepressant treatment by a course of electroconvulsive therapy (ECT) and compared to age- and sex-matched controls (n=20). - Results - The patients with depression showed lower mean VEGF levels in the CSF prior to ECT than the controls (p=0.041). Regarding the patients, CSF VEGF concentration at baseline and after the complete ECT treatment did not differ from each other (p=0.78). - Limitations - Major limitations of this study are the small sample size and that data from corresponding serum levels cannot be provided. Another limitation is that the controls were not completely healthy, as they were recruited from a memory clinic with subjective complaints. The timing of the second sample might have been suboptimal, when taking into account that there might be an on-going phase of re-equilibrating after ECT. - Conclusions - CSF VEGF concentrations were lower in a clinical sample of patients with treatment-resistant depression compared with matched controls. Additionally, no change in CSF VEGF levels during a course of ECT could be detected.
Available online 18 Apr 2019
Gesehen am 21.01.2020